An exploration of the need for and cost of selected trade facilitation measures in Asia-Pacific in the context of the WTO negotiations - Yann Duval (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
This paper presents the findings and results of an exploratory ARTNeT study on the needs for and costs of implementation of selected trade facilitation measures (TFMs) related to GATT Articles V, VIII and X. This summary paper is based on six ARTNeT working papers issued between January and April 2006, including five country case studies (available at www.artnetontrade.org).
Keywords: F1; 330; WTO; Trade Facilitation; GATT Articles V; VIII and X